Effects of Vacuum Processing Treatment on the Structure and Physical and Chemical Properties of Fresh Waxy Corn Starch - Ruihang XU; Libin ZHU; Dan ZHU; Wenyi WEI; Guangcai NIU; Chenyu ZHAO; Yufan ZHANG (Shipin gongye ke-ji)
In order to explore the effect of vacuum processing treatment on the starch structure and physical and chemical properties of fresh waxy corn, Huangnuo 619 and Heibao were used as raw materials. The microstructure and physicochemical properties of fresh waxy corn starch after vacuum processing treatment were investigated by scanning electron microscope, X-ray diffractometer, Fourier infrared spectrometer, differential scanning calorimeter and rapid viscosity analyzer. The results showed that vacuum processing treatment of Huangnuo 619 and Heibao fresh waxy corn significantly increased the amylope content (P<0.05), from 5.39% and 6.26% to 8.52% and 9.71% respectively, and significantly decreased the amylopectin content (P<0.05), from 94.61% and 93.74% to 91.48% and 90.29% respectively. Starch particles were damaged severely, the crystal type and functional group structure of starch had not been changed, but the relative crystallinity decreased by 9.62% and 9.41% respectively. After vacuum processing treatment, the initial temperature, peak temperature, final temperature and gelatinization enthalpy of the two kinds of fresh waxy corn starch decreased significantly (P<0.05), and the gelatinization temperature, peak viscosity, final viscosity, decay value and recovery value decreased significantly (P<0.05), which showed that starch was more prone to gelatinization and its anti-aging ability was enhanced. In addition, the resistant starch (RS) of fresh waxy corn starch was transformed into rapid digestible starch (RDS) and slow digestible starch (SDS) by vacuum processing treatment, indicated that the digestion rate of fresh waxy corn starch could be improved by vacuum processing treatment. The experimental results can provide theoretical basis for vacuum processing and utilization of fresh waxy corn.